The Prevalence and Genetic Spectrum of Familial Hypercholesterolemia in Qatar Based on Whole Genome Sequencing of 14,000 Subjects - Diboun, Ilhame; Al-Sarraj, Yasser; Toor, Salman M.; Mohammed, Shaban; Qureshi, Nadeem; Al Hail, Moza S. H.; Jayyousi, Amin; Al Suwaidi, Jassim; Albagha, Omar M. E. (Frontiers in Genetics, 2022)
Familial hypercholesterolemia (FH) is an inherited disease characterized by a reduced efficiency of low-density lipoprotein-cholesterol (LDL-C) removal from the blood and consequently, an increased risk of life-threatening early cardiovascular complications. In Qatar, the prevalence of FH has not been determined and the disease, as in many countries, is largely underdiagnosed. In this study, we combined whole genome sequencing data from the Qatar Genome Program with deep phenotype data from Qatar Biobank for 14,056 subjects to determine the genetic spectrum and estimate the prevalence of FH in Qatar. We used the Dutch Lipid Clinic Network (DLCN) as a diagnostic tool and scrutinized 11 FH-related genes for known, and possible, pathogenic mutations. Results revealed an estimated prevalence of 0.8% (1:125) for definite/probable cases of FH in the Qatari population. We detected 16 known pathogenic/likely pathogenic mutations in LDLR and one in PCSK9; all in a heterozygous state with high penetrance. The most common mutation was rs1064793799 (c.313+3A>C) followed by rs771019366 (p.Asp90Gly); both in LDLR. In addition, we identified 18 high penetrant possible pathogenic variants, of which 5 were Qatari-specific, in LDLR, APOB, PCSK9, and APOE which are predicted to be among the top 1% most deleterious mutations in the human genome, but further validation is required to confirm their pathogenicity. We did not detect any homozygous FH or autosomal recessive mutations in our study cohort. This pioneering study provides a reliable estimate of FH prevalence in Qatar based on a significantly large population-based cohort, whilst uncovering the spectrum of genetic variants associated with FH.